IN VITRO PROPAGATION AND SECONDARY METABOLITES INVESTIGATION OF HYPERICUM PERFORATUM L. - Mohammed, Namam Rebaz; Dalar, Abdullah; Ozdemir, Fethi Ahmet; Turker, Musa (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2019)
Hypericum perforatum L. was regenerated in plant tissue culture and secondary metabolites (hypericin, pseudohypericin, quercetin, rutin, and chlorogenic acid) of the plants collected from field and regenerated in vitro were quantitatively compared. The liquid, semi solid and solid form of Murashige and Skoog (MS) basal medium supplemented with plant growth regulators (PGRs) in different concentration and combination were employed for regeneration and secondary metabolite product amplification. Based on preliminary tests nodal segment was preferred as an explant. At the end of 50 days of regeneration period, no statistically significant difference was observed between the length of root and shoot and root number of plants regenerated in solid, semi solid and liquid media supplemented with different PGRs. The quantitative secondary metabolite analyses was performed by High Performance Liquid Chromatography (HPLC). The highest concentrations of chlorogenic acid, quercetin, and pseudohypericin were observed in shoots and roots of the plants collected from field. Whereas the compounds were detected in low quantity in plants regenerated in the liquid, semi solid and solid medium, except for quercetin which was found higher concentration than chlorogenic acid, quercetin, and pseudohypericin in vitro regenerated plants. Hypericin and rutin were not detected by HPLC analysis in all of plants regenerated in vitro and in vivo.
Keywords: Hypericum perforatum L.; secondary metabolite; in vitro propagation; Environmental Sciences & Ecology